Praising the process: can effort-graded feedback improve the motivation, engagement and attainment of students with the formative assessment process? - Bayliss, S (2016)
This study built on a previous piece of my research, which found that student perceptions of the efficacy of feedback do not always match what both teachers and the literature might expect. A new model of written feedback was implemented in the classroom that praises the process of learning as opposed to the outcome. 2 collaborating teachers implemented a criteria-driven effort grade feedback intervention in conjunction with standard practice of constructive written comments. 50 year-10 students from 2 mixed attainment science sets were studied in terms of their motivation for learning, engagement with the feedback process and resulting attainment before and after intervention. The effectiveness of the intervention was assessed using action research methodology in two cycles gathering evidence from the collaborating teacher and students using interviews and questionnaires. Analysis of the data showed that reactions to the intervention from both teachers and students were positive. Students initially struggled to identify and reflect on their own effort, often over-estimating it when compared to teacher assessment. Throughout the intervention, however, refinements to the effort-criteria, based on evidence gathered in the action research process, enabled increased student awareness of effort and ability to apply consistent grading. Motivation to learn improved and homework completion rates increased from 35% to 90%. Students showed better engagement with the feedback process and increased reflection and utilisation of written comments. A marginal increase in attainment was noted, though the limitations in using this as a measure with a small sample and short duration are discussed. Contemporary educational research and implications for future practice are discussed; wider-use of effort-grading in feedback is indicated to verify findings in different subject areas. Teacher collaboration is crucial in achieving this and the practicalities of larger-scale roll-out are considered.